2017
DOI: 10.1007/s10508-017-1023-4
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Work, Gender Roles, and Intimate Partner Violence in Nigeria

Abstract: The purpose of this study was to determine the contribution of women's labor force participation to the risk of intimate partner violence (IPV) victimization in the past 12 months, using data for 20,635 currently married women aged 15-49 years from the 2013 nationally representative Nigeria Demographic and Health Survey. Multilevel logistic regression models of sexual and physical IPV, with interactions between women's work and social norms regarding traditional gender roles, were developed. Approximately 23% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 52 publications
3
35
3
Order By: Relevance
“…These 2 findings may be linked, as younger women are less likely to be economically independent from their partners. In contrast with our findings and other literature documenting a protective association between employment and IPV [33], some previous work has suggested that female employment may increase risk of IPV due to perceived power imbalances by the spouse [58,59]. However, in the context of drought, it may be that the woman's income contributes to household resilience to poverty and food insecurity associated with drought, which in turn decreases risk for violence.…”
Section: Discussioncontrasting
confidence: 99%
“…These 2 findings may be linked, as younger women are less likely to be economically independent from their partners. In contrast with our findings and other literature documenting a protective association between employment and IPV [33], some previous work has suggested that female employment may increase risk of IPV due to perceived power imbalances by the spouse [58,59]. However, in the context of drought, it may be that the woman's income contributes to household resilience to poverty and food insecurity associated with drought, which in turn decreases risk for violence.…”
Section: Discussioncontrasting
confidence: 99%
“…Women in this community who experience IPVAW are more likely to be employed, have more children, and not cohabiting with their partner. Employment status has had mixed associations in studies throughout the world [2932] and not associated with IPVAW in northeastern Brazil. [33] The unclear association of women’s employment status may be due to the complex interplay of socioeconomics and gender norms.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical complexity of women’s employment status and its implication on relationship dynamics mirrors the inconsistent associations found in previous studies. [32,34]…”
Section: Discussionmentioning
confidence: 99%
“…The picture from observational studies examining the links between a woman's economic circumstances and her current IPV risk is similarly complex [7]. For example, women's employment or working for money has been associated with lower violence in some settings [29] but higher in others [19,[29][30][31][32] with some suggestion that formal employment may be more protective than irregular or seasonal employment [33] and longer duration of employment more protective than shorter [34]. Other studies from a range of countries indicate no association between women's employment or income and IPV [19,29,35].…”
Section: Introductionmentioning
confidence: 99%